Reflexões sobre as consequências da implantação de grandes empreendimentos no município de Anchieta-ES - Alvarenga, Andréa Curtiss (2010)
Since the discovery of oil reserves in the coastline, the State of Espírito Santo is experiencing an economic re-structuring that affects all of its territorial extension. For this re-structuring, and in view of its insertion in the global network of econ